A CLINICAL STUDY TO EVALUATE THE EFFICACY OF TRITIYA ALAMBUSHADI CHURNA IN MANAGEMENT OF AMAVATA - Vaibhav, *Phartale; Rachana, Patil; Patil, Kavita; Shinde, Kiran (International Journal of Ayurveda and Pharma Research, 2017)
Amavata is a chronic disease. Due to tremendous pain in Amavata, patients daily life get disturbed. Also the morbidity of disease disturbs routine work of the patient. The sign and symptoms of Amavata is nearer to resemble with Rheumatoid arthritis in modern science, R.A is more than just arthritis. The prevalence of R.A. is approximately 0.8% of the population (range 0.3 to 2.1%), woman are affected three times more often than man. Family studies indicate a genetic predisposition. Now a days, due to changed life style and improper dietary habits like pattern of spicy food, irregular timing of meals, over eating etc. causes Agnimandya and it leads to production of Ama. All these faulty eating habits are almost always accompanied with faulty vihara like improper or over exercise, late night parties, suppression of natural urges, excessive traveling etc. these are causes of vitiation of Vata. This vitiated Vata carries Ama to the all over the body especially the Kapha sthanas and produces symptoms like Sandhi shotha, Sandhi shula, Stabdhata1 (stiffness) and other systemic sign and symptoms. This dreadful disease is called as Amavata. Tritiya Alambushadi Churn provided highly significant relief in pain (73.41%). joint score (59.26%), tenderness (73.91%), stiffness (76.22%), swelling of joints (78.53%), local temperature (77.61%) and improvement in grip strength (73.61%),functional activity (79.66%). i.e. overall total improvement is 73.63%. On the basis of these observations, administration of Tritiya Alambushadi Churna is effective for the management of Amavata.